Psycho-cardiovascular interaction network in cardiovascular health and disease: signaling pathways and molecular mechanisms - Zexi Li; Fanghui Li; Chunyi Yan; Lianrui Xiang; Aobo Gong; Ying Cao; Yifan Zhou; Wei Zhang; Rui Zeng (Precision Clinical Medicine, 2026)
Abstract Extensive evidence indicates a strong association between psychological and psychiatric factors and cardiovascular disease (CVD). Psychological and psychiatric factors, including depression, anxiety, and chronic stress, are associated with an increased risk of CVD and adverse cardiovascular outcomes. Furthermore, this association is bidirectional, as patients with CVD have a notably higher risk of developing comorbid mental disorders. We propose the psycho-cardiovascular interaction network (PCIN) to elucidate the multilevel integrated regulatory mechanisms linking psychological status and cardiovascular function. In this Review, we synthesize epidemiologic evidence, summarize the major mechanisms through which these factors may influence cardiovascular function, and focus on key signaling pathways within the PCIN, including BDNF, PROK/PKR, MAPK, 5-HT/5-HT2A-R, and NLRP3 inflammasome pathways, which may mediate bidirectional brain–heart communication and mental disorder–CVD comorbidity. On the basis of the PCIN framework, we discuss integrated intervention strategies, including non-pharmacological approaches and molecularly targeted therapies for brain–heart axis-informed management. Future research should focus on the translational potential of psycho-cardiovascular regulatory molecules as therapeutic targets and candidate biomarkers, and high-quality studies are urgently needed to elucidate the long-term effects of psychological interventions on cardiovascular health outcomes and their molecular mechanisms. In addition, integrating psychosocial phenotypes with molecular biomarkers may facilitate individualized risk assessment and inform brain–heart axis-based prevention and therapeutic strategies.